Disseminated cryptococcosis manifested as a single tumor in an immunocompetent patient, similar to the cutaneous primary forms - Danielle Mechereffe do Amaral; Ritha de Cássia Capelato Rocha; Luiz Euribel Prestes Carneiro; Dewton Moraes Vasconcelos; Marilda Aparecida Milanez Morgado de Abreu (Sociedade Brasileira de Dermatologia, 2016)
Abstract Cryptococcosis is a fungal infection caused by Cryptococcus neoformans that tends to affect immunocompromised individuals. The fungi are mostly acquired by inhalation, which leads to an initial pulmonary infection. Later, other organs - such as the central nervous system and the skin - can be affected by hematogenous spread. In addition, cutaneous contamination can occur by primary inoculation after injuries (primary cutaneous cryptococcosis), whose diagnosis is defined based on the absence of systemic involvement. The clinical presentation of cutaneous forms typically vary according to the infection mode. We report an unusual case of disseminated cryptococcosis in an immunocompetent patient with cutaneous lesions similar to those caused by primary inoculation. This clinical picture leads us to question the definition of primary cutaneous cryptococcosis established in the literature.